The effectiveness of dialectical Behavior therapy approach (Mindfulness) in changing attitudes towards youth immigration - abdulmahdi Mohammad ali, Zahraa (Al-Adab Journal, 2020)
The search aims to identify the effectiveness of mindfulness dialectical Behaviour therapy in changing attitudes to wards immigration. The sample consisted of (15) student in the age of (22) years, it was distributed on experimental group (8) student , and control group ( 7) students , to achieve the objectives of current study , the researcher developed two measures (mindfullness and attitudes toward immigrant) and extract the psychometric characters for them, and verified homogeneity between the two groups in (mindfullness and attitudes toward immigrant ) . The mindfulness training program prepared by the researcher, of ( 16) sessions are set up in the frame. work if dialectical behavior therapy . the result showed that the program in changing attitudes toward immigrant among students, in the light of these findings the research put forward set of recommendations and proposals.